A Comparison of the Self-Esteem Levels in Evangelical Christian and General Populations - Aycock, David W. (Journal of psychology and theology, 1985)
Self-esteem is a central mechanism in psychological health and is reported to be readily accessible to Christians due to their unique relationship with an unconditionally accepting God. The self-esteem levels of 351 evangelical Christians from college and church settings and 1115 general volunteers comprised of students, administrators, and government employees were measured by the Self-Esteem scale of the Coping Resources Inventory for Stress. Analysis of variance indicated that the more highly educated graduate student and academic administrator subgroups of the general population outdistanced several other general subgroups and accounted for the significant differences between the two large populations. The mean scores of the Christian subgroups were not significantly different from each other nor from any general subgroups, but fluctuated as a function of educational level in a pattern consistent with the general population. Personal attainments are offered as a prominent antecedent of self-esteem and the findings are discussed in terms of the inadequacies of cognitive change alone to produce practical gains in this attribute and the relative stability of the self-esteem trait